Defective Tapetum Cell Death 1 (DTC1) Regulates ROS Levels by Binding to Metallothionein during Tapetum Degeneration. Issue 3 (23rd December 2015) - Yi, Jakyung; Moon, Sunok; Lee, Yang-Seok; Zhu, Lu; Liang, Wanqi; Zhang, Dabing; Jung, Ki-Hong; An, Gynheung
Abstract : Timely production of superoxides is essential for initiation of tapetum degeneration in rice. Abstract: After meiosis, tapetal cells in the innermost anther wall layer undergo program cell death (PCD )-triggered degradation. This step is essential for microspore development and pollen wall maturation. We identified a key gene, Defective Tapetum Cell Death 1 ( DTC1 ), that controls this degeneration by modulating the dynamics of reactive oxygen species (ROS ) during rice male reproduction. Mutants defective in DTC1 exhibit phenotypes of an enlarged tapetum and middle layer with delayed degeneration, causing male sterility. The gene is preferentially expressed in the tapetal cells during early anther development. In dtc1 anthers, expression of genes encoding secretory proteases or lipid transporters is significantly reduced, while transcripts of PCD regulatory genes, e.g. UDT1, TDR1, and EAT1 / DTD, are not altered. Moreover, levels of DTC1 transcripts are diminished in udt1, tdr, and eat1 anthers. These results suggest that DTC1 functions downstream of those transcription factor genes and upstream of the genes encoding secretory proteins. DTC1 protein interacts with OsMT2b, a ROS scavenger. Whereas wild-type plants accumulate large amounts of ROS in their anthers at Stage 9 of development, those levels remain low during all stages of development in dtc1 anthers. These findings indicate that DTC1 is a key regulator for tapetum PCD by inhibiting ROS -scavenging activity.